Marx e a Rússia revolucionária - Leônidas Dias de Faria (2017)
In his last decade and a half, Marx turned to the detailed examination of the Russian reality of his time and to the revolutionary proposals of its main critical interpreters, the so-called populists, especially Nikolai Chernichevsky. As a result, the philosopher drew to the country an unusual prognosis, if one thinks from the traditional readings of his work as a whole, according to which a Russian revolutionary process based on its archaic communal agrarian formations was possible, plausible, desirable and probable, by means of direct appropriation of modern Western productive forces, under the guidance of the triply engaged populist Intelligentsia: in the emancipation of the peasant communes themselves, in the emancipation of Russia as a whole, and finally in the global human emancipation, intent that was attested to by its firm participation in the international revolutionary movement. In accordance with the fundamental orientation of this intelligentsia, which in his assessment forms the ideological dimension of the then European revolutionary vanguard, the Russian socialist movement, Marx also espouses this Russian revolution as the fuse of a Western proletarian revolutionary process that would complement that in a global process with expected repercussions on the colonized periphery of the world capitalist system, in countries like India and many others, whose remaining communal forms would serve as foci of resistance and starting points for local social regeneration at the same time able for an equally global articulation. The present work is the result of an effort to bring to light, albeit partially, that moment and dimension that are little known and still less understood from Marx's theoretical production and practice.